USING MATIFIC FOR MATHEMATICS LEARNING: SYSTEMATIC LITERATURE REVIEW AND BIBLIOMETRIC ANALYSIS - Nursyifa, Nursyifa; Rosiana Mufliva; Robandi, Babang (EMTEKA: Jurnal Pendidikan Matematika, 2026)
Research related to the use of the Matific platform in mathematics learning is still scattered with diverse focuses and contexts. The study aims to map the use of the Matific digital platform in mathematics learning through a Systematic Literature Review (SLR) combined with bibliometric analysis using the PRISMA protocol. The findings show that Matific is most widely used at the primary school level, with research concentrated in Brazil and Indonesia as the two countries with the highest number of publications. This platform consistently has a positive impact on student motivation and engagement in all studies reviewed, while improvements in student learning outcomes and conceptual understanding of mathematics are also widely reported, albeit with varying degrees of effectiveness depending on the different implementation contexts. These findings indicate that the effectiveness of Matific is highly dependent on the quality of pedagogical integration, teacher readiness, and the availability of technological infrastructure, rather than solely on the platform itself. Penelitian terkait penggunaan platform Matific dalam pembelajaran matematika masih tersebar dengan fokus dan konteks yang beragam. Penelitian bertujuan untuk memetakan penggunaan platform digital Matific dalam pembelajaran matematika melalui Systematic Literature Review (SLR) yang dikombinasikan dengan analisis bibliometrik menggunakan protokol PRISMA. Temuan menunjukkan bahwa Matific paling banyak digunakan pada jenjang sekolah dasar, dengan penelitian yang terkonsentrasi di Brasil dan Indonesia sebagai dua negara dengan jumlah publikasi terbanyak. Platform ini secara konsisten memberikan dampak positif terhadap motivasi dan keterlibatan siswa pada seluruh studi yang ditinjau, sementara peningkatan hasil belajar dan pemahaman konseptual matematika siswa juga banyak dilaporkan meskipun dengan tingkat efektivitas yang bervariasi bergantung pada konteks implementasi yang berbeda. Temuan ini mengindikasikan bahwa efektivitas Matific sangat bergantung pada kualitas integrasi pedagogis, kesiapan guru, dan ketersediaan infrastruktur teknologi, bukan semata-mata pada platform itu sendiri.